Environmentally Sustainable Regional Development Management - Sumarna, Andri; Haryono, Merda Budi; Fauzi, Sudar; Hanapia, Cepi; Lestari, Dewi Astri (Jurnal Economic Resource, 2022)
Environmental degradation in Indonesia is becoming increasingly alarming due to growing demographic pressures, industrialisation, and weak natural resource management. This study aims to analyse the factors causing environmental degradation and formulate strategies for environmentally sustainable regional development as a means of achieving sustainability. This study employs a literature review method, drawing from 45 relevant scientific documents, books, and government policies. Literature selection was conducted using purposive sampling based on topic relevance and depth of analysis. The analysis was conducted thematically to identify patterns of relationships between demographic, economic, socio-cultural, and institutional factors and environmental conditions. The results of the study indicate that environmental degradation in Indonesia is the result of complex interactions between these factors, which reinforce each other. Environmental development efforts will only be effective if they are systematically integrated into national and regional development strategies, combining ecological perspectives, environmentally friendly technological innovations, good governance, and ethical values and local wisdom. The implications of this research emphasise the need to strengthen cross-sectoral synergies, public participation, and the adoption of clean technology as key pillars in maintaining ecosystem sustainability while promoting inclusive economic growth.